Kebijakan Moneter dan Strategi Penanggulangan Kemiskinan dalam Kepemimpinan Umar bin Khattab - Hidayat, Nurul; Khalida, Nur Diana; Firdaus, Jannatul; Najiatun, Najiatun; Awan, Edi; Khas, As’adi; Arif, Hertin Khalifatun Nisa; Fauziyah, Hanifah (JIOSE: Journal of Indonesian Sharia Economics, 2025)
The leadership of Umar ibn al-Khattab is undeniable as a statesman capable of formulating new regulations and revising those established during the time of the Prophet Muhammad and Abu Bakr. During his rule, poverty was significantly reduced through the application of sound economic principles. This study employs a library research method and descriptive analysis using books, journals, and papers related to the economic policies of Umar ibn al-Khattab. The research discusses monetary policies and poverty alleviation strategies during his reign. The monetary policy included the establishment of currency as an effort to stabilize the economy, while poverty alleviation strategies were carried out through strengthening the independence of the baitul mal (public treasury) and utilizing land to increase state revenue. The persistent issue of poverty, which remains difficult to overcome in modern economic systems, had already been a serious concern during Umar ibn al-Khattab’s leadership. The findings of this study indicate that the economic policies of his era remain relevant as references for addressing poverty through resource management and transparent, productive public financial governance.